Characterization of the somatostatin-like immunoreactivity extracted from an adrenal medullary tumour. Issue 3 (March 1982) - Corder, R.; Sykes, J. E. C.; Lowry, P. J.
Abstract : Significant amounts of somatostatin-like immunor reactivity (SLI) were detected in the extract of a human catecholamine-secreting adrenal medullary tumour. After salt fractionation and reconstitution the major portion of SLI was purified by gel filtration and two HPLC steps; in all three systems it eluted in the position of somatostatin-14. The purified somatostatin-like peptide inhibited, in a dose-related manner, growth hormone release from stimulated perfused rat anterior pituitary ceils in vitro. Amino acid analysis showed the purified peptide to have an identical composition to somatostatin found in other species.